Alkylating Reagents Employed in Catellani‐Type Reactions - Liu, Ze‐Shui; Gao, Qianwen; Cheng, Hong‐Gang; Zhou, Qianghui (Chemistry : a European journal, 2018)
The Catellani reaction is a powerful strategy that allows the expeditious synthesis of highly substituted arenes, which are not easily accessible through traditional transition‐metal‐catalyzed cross‐coupling reactions. This reaction utilizes the synergistic interplay of palladium and norbornene catalysis to facilitate sequential ortho‐C−H functionalization and ipso termination of aryl iodides in a single operation. Since pioneering work by the group of Catellani in 1997, and later by the group of Lautens, this chemistry has attracted considerable attention from the synthetic chemistry community. Dramatic progress has been made by a number of groups in the past two decades. In this Minireview, the alkylating reagents employed in this intriguing reaction and the corresponding applications in organic synthesis are summarized; thus complementing existing reviews to inspire future developments. Changing conventions: The Catellani reaction, such as depicted, is a powerful strategy that allows the expeditious synthesis of highly substituted arenes, which are not easily accessible through traditional transition‐metal‐catalyzed cross‐coupling reactions (NBE=norbornene). This review highlights the alkylating reagents employed in these reactions and related applications in organic synthesis.